Lyapunov-Based Output Feedback Learning Control of Robot Manipulators - Dogan, K. Merve; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan; Cetin, Kamil (IEEE, 2015)
This paper address the output feedback learning tracking control problem for robot manipulators with repetitive desired joint level trajectories. Specifically, an observer-based output feedback learning controller for periodic trajectories with known period have been proposed. The proposed learning controller guarantees semi-global asymptotic tracking despite the existence of parametric uncertainties associated with the robot dynamics and lack of velocity measurements. A learning-based feedforward term in conjunction with a novel observer formulation is designed to obtain the aforementioned result. The stability of the controller-observer couple is guaranteed via Lyapunov based arguments. Numerical studies performed on a two link robot manipulator are also presented to demonstrate the viability of the proposed method.
American Control Conference -- JUL 01-03, 2015 -- Chicago, IL
Keywords: Nonlinear-Systems